Some safety aspects of enterococci isolated from Slovak lactic acid dairy product "žinčica" - Lauková, Andrea; Kandričáková, Anna; Bino, Eva; Tomáška, Martin; Kološta, Miroslav; Kmeť, Vladimír; Strompfová, Viola (Folia microbiologica, 2020)
In Slovakia, dairy products made from ewes' milk have a long tradition. These products include the lactic acid product called "žinčica" which is a by-product occurring during the preparation of ewes' lump cheese. There is no information in the literature regarding the special properties of the microbiota, especially lactic acid Firmicutes, which can survive in "žinčica." From the safety aspect, enterococci are a controversial group of bacteria, and those from "žinčica" have never been tested for their properties. The "žinčica" used in our study was supplied by several different agrofarms producing ewes' lump cheese in central Slovakia. The species Enterococcus faecium (strains EF30E1, EF32E1, EF34E1, EF34E5) and Enterococcus faecalis (strains EE30E4, EE35E1, E31E2, altogether 7) were detected in samples from "žinčica" identified using MALDI-TOF spectrometry with secure genus identification/probable species identification and then confirmed by means of PCR. Enterococci were hemolysis-negative and the genes of the typical enterococcal virulence factors were mostly absent; the gelE gene was found in two E. faecium strains (EF30E1 and EF32E1), the agg gene was detected in E. faecalis EE35E1, and the esp gene was found in two E. faecalis strains (EE30E4 and EE31E2). No strains harbored the cytolysin A gene. Biofilm formation was detected in four strains (EF30E1, EF32E1, EF34E1, and EF34E5), indicating highly positive and low-grade positive biofilm formation. Enterococci were mostly susceptible to antibiotics tested for their phenotype. This is the first study to analyze enterococci in "žinčica."
Keywords: Virulence Factors; Anti-Bacterial Agents; Enterococcus faecium; ovce; potravinářská mikrobiologie; Food Microbiology; biofilmy; Microbial Sensitivity Tests; Microbiota; Cheese; mikrobiota; Bacterial Proteins; Slovakia; Slovenská republika; sýr; ženské pohlaví; zvířata; Biofilms; bezpečnost potravin; antibakteriální látky; Sheep; Enterococcus faecalis; mikrobiální testy citlivosti; faktory virulence; Enterococcus; Female; bakteriální proteiny; Food Safety; Animals